Üzleti és PR etika. Az üzleti, a kommunikációs szakmai és a PR etika aktuális kérdései - Buday-Sánhta , Andrea (Kultúratudományi Szemle, 2022)
Business and PR Ethics Andrea Buday-Sántha Economic, political, environmental and technological transformations, that take place both domestically and globally as well as focus on the role of the cultural value crises and value changes, institutions and norms of ethics. It intends to point out the tendencies in the field of ethics, business and PR ethics, their causes and to their current phenomena, it clarifies the basic ethical values, the process of institutionalizing ethics, the practical phenomena and the challenge of ethics. It is a tendency of contradiction that the development of ethical institutions is fuelled by the devaluation of human and ethical values and new phenomena of our changing world. With the introduction of ethical institutions for professions, markets and organizations, - in this way, by demonstrating and publishing core values and applying innovative, evolving insurance solutions -, they protect existing ethical values, also curb the effects of negative trends, and thirdly, weakening individual, organizational, market and social morality.